2020
DOI: 10.1371/journal.pone.0239423
|View full text |Cite
|
Sign up to set email alerts
|

After providing end of life care to relatives, what care options do family caregivers prefer for themselves?

Abstract: Objectives We examined how caregivers who had cared for a relative at end of life (EoL) wished to be cared for in the event that they experienced advanced dementia or physical disability in the future, and what factors influenced their preferences for EoL care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 66 publications
0
8
0
1
Order By: Relevance
“…The significant discrepancy between these results suggests that legalization of PAS may produce significant shifts in the attitudes of caregivers towards this practice, regardless of their earlier attitudes; moreover, such attitudes and shifts are unlikely to be uniform, and may be crucially influenced by variables such as sex and ethnicity (Owen et al, 2001;Wicher and Meeker, 2012;Stolz et al, 2015;Cohen-Mansfield and Brill, 2020) as well as by individual political and religious beliefs (Kemmelmeier et al, 2002;Richter et al, 2001;O'Dwyer et al, 2016). These are not independent of each other; for example, a survey of African-Americans found that several factors, including their cultural and spiritual values and their attitude towards the healthcare system, influenced their lower preference for euthanasia or PAS (Wicher and Meeker, 2012).…”
Section: Caregiver Burdenmentioning
confidence: 97%
See 4 more Smart Citations
“…The significant discrepancy between these results suggests that legalization of PAS may produce significant shifts in the attitudes of caregivers towards this practice, regardless of their earlier attitudes; moreover, such attitudes and shifts are unlikely to be uniform, and may be crucially influenced by variables such as sex and ethnicity (Owen et al, 2001;Wicher and Meeker, 2012;Stolz et al, 2015;Cohen-Mansfield and Brill, 2020) as well as by individual political and religious beliefs (Kemmelmeier et al, 2002;Richter et al, 2001;O'Dwyer et al, 2016). These are not independent of each other; for example, a survey of African-Americans found that several factors, including their cultural and spiritual values and their attitude towards the healthcare system, influenced their lower preference for euthanasia or PAS (Wicher and Meeker, 2012).…”
Section: Caregiver Burdenmentioning
confidence: 97%
“…Further searches were conducted within these results using the additional search terms "caregiver," "caregiver burden," "stress," "behavioral and psychological symptoms of dementia," "BPSD," "economic," "financial," "autonomy," "dignity," "identity," "personhood" and "ethics." By this method, a total of 103 citations were retained (Pereira, 2011;Schuurmans et al, 2021;Kemmelmeier et al, 2002;Bradley, 2009;Baeke et al, 2011;Chakraborty et al, 2017;Madadin et al, 2020;Nichols, 2013;Emanuel et al, 2000;Krag, 2014;Trachtenberg and Manns, 2017;Bilchik, 1996;Lazar and Davenport, 2018;Karrer et al, 2020;Stakišaitis et al, 2019;Finucane et al, 2007;Finucane, 1999;Sachs et al, 2004;Dominguez et al, 2021;Meier, 1997;Liu et al, 2020;Gao et al, 2019;Gilhooly et al, 2016;Watson et al, 2019;Cheng, 2017;Biggs et al, 2019;Fam et al, 2019;Dening et al, 2013;Owen et al, 2001;Cohen-Mansfield and Brill, 2020;Anderson et al, 2019;O'Dwyer et al, 2016;Bravo et al, 2018;Wicher and Meeker, 2012;Stolz et al, 2015;Seike et al, 2021;Kashimura et al, 2021;Zwingmann et al, 2018;…”
Section: Pitfalls Inherent In the Practice Of Pas In The Specific Case Of Dementiamentioning
confidence: 99%
See 3 more Smart Citations